The Relationship between Interleukin-18 Polymorphisms and Allergic Disease: A Meta-Analysis. (5th June 2014) - Cheng, Daye; Hao, Yiwen; Zhou, Wenling; Ma, Yiran
Abstract : Recent studies have suggested that IL-18 −607C/A and −137G/C polymorphisms may be associated with the risk of allergic disease; however, individually published results are inconclusive. Therefore, we performed a meta-analysis to clarify whether IL-18 −607C/A and −137G/C polymorphisms were associated with the risk of allergic disease. A total of 21 studies including 5, 331 cases and 9, 658 controls were involved in this meta-analysis. In the overall analysis and the subgroup analysis according to ethnicity, we did not find significant association between IL-18 −607C/A or −137G/C polymorphism and the risk of allergic disease (all P > 0.05 ). However, in a stratified analysis by type of allergic disease, our results indicated that IL-18 −607C/A polymorphism was associated with a significantly decreased risk of allergic asthma in heterozygous comparison and IL-18 −137G/C was associated with a significantly decreased risk of allergic dermatitis in recessive model and homozygous comparison. In the stratified analysis by source of control, IL-18 −607C/A showed significantly reduced risk in population-based subgroup, and for IL-18 −137G/C only significantly decreased risk was found in the hospital-based subgroup. Our meta-analysis suggests that IL-18 −607C/A and −137G/C polymorphisms may be protective factors for the risk of allergic asthma and allergic dermatitis, respectively.